The relationship between real-world labs, real-world experiments and urban planning, using the example of cooperative open space development - Räuchle, Charlotte (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
This paper examines the relationship between real-world laboratory and planning and highlights the potentials that real-world experiments offer to urban planning. It is based on a case study on cooperative open space development to unite residents and strengthen social cohesion in superdiverse neighbourhoods. Although the subject of „experiment and planning“ has received increasing attention recently, there is still a lack of theoretical and empirical analysis. Therefore, this study, first, addresses the relationship between experiment and planning from a conceptual perspective – regarding objectives, types of knowledge, methods of knowledge production, instruments and processes. Second, based on the case study, the content, instrumental and actor-related dimensions of this relationship are analysed. The results show that real-world experiments can open up opportunities for urban planning – in terms of content (production of more differentiated knowledge), instruments (provision of more open participation formats), and actors (formation of new governance arrangements). Whether this is really seen as an opportunity, however, depends on the local planning object and, in particular, on the local planning culture.